Abgeleitete Textformate: Text und Data Mining mit urheberrechtlich geschützten Textbeständen - Christof Schöch; Frédéric Döhl; Achim Rettinger; Evelyn Gius; Peer Trilcke; Peter Leinen; Fotis Jannidis; Maria Hinzmann; Jörg Röpke (Zeitschrift für digitale Geisteswissenschaften, 2016)
Despite the TDM exception in German copyright law, Text and Data Mining (TDM) with copyrighted texts is still subject to restrictions, including those concerning the storage, publication and follow-up use of the resulting corpora, leaving the full potential of TDM in the Digital Humanities untapped. We propose derived text formats as a solution: here, copyrighted textual materials are transformed in such a way that copyright-relevant features are removed, but that the use of various relevant methods of TDM remains possible. Several derived text formats are examined from the perspectives of Computational Literary Studies, Computer Science, memory institutions and Law.